Chemically induced cone degeneration in the 13-lined ground squirrel - Follett, Hannah M.; Warr, Emma; Grieshop, Jenna; Yu, Ching Tzu; Gaffney, Mina; Bowie, Owen R.; Lee, Jong Won; Tarima, Sergey; Merriman, Dana K.; Carroll, Joseph (Visual neuroscience, 2024)
Animal models of retinal degeneration are critical for understanding disease and testing potential therapies. Inducing degeneration commonly involves the administration of chemicals that kill photoreceptors by disrupting metabolic pathways, signaling pathways, or protein synthesis. While chemically induced degeneration has been demonstrated in a variety of animals (mice, rats, rabbits, felines, 13-lined ground squirrels (13-LGS), pigs, chicks), few studies have used noninvasive high-resolution retinal imaging to monitor the in vivo cellular effects. Here, we used longitudinal scanning light ophthalmoscopy (SLO), optical coherence tomography, and adaptive optics SLO imaging in the euthermic, cone-dominant 13-LGS (46 animals, 52 eyes) to examine retinal structure following intravitreal injections of chemicals, which were previously shown to induce photoreceptor degeneration, throughout the active season of 2019 and 2020. We found that iodoacetic acid induced severe pan-retinal damage in all but one eye, which received the lowest concentration. While sodium nitroprusside successfully induced degeneration of the outer retinal layers, the results were variable, and damage was also observed in 50% of contralateral control eyes. Adenosine triphosphate and tunicamycin induced outer retinal specific damage with varying results, while eyes injected with thapsigargin did not show signs of degeneration. Given the variability of damage we observed, follow-up studies examining the possible physiological origins of this variability are critical. These additional studies should further advance the utility of chemically induced photoreceptor degeneration models in the cone-dominant 13-LGS.